The impact of Covid-19 on the lives of workers in the Garment Industry: a rapid survey jointly conducted by BRAC University's CED and JPGSPH and the Subir and Malini Chowdhury Center for Bangladesh Studies at the University of California, Berkeley - Rabbani, Atonu; Saxena, Sanchita Banerjee; Islam, MD. Faizul (Centre for Entrepreneurship Development (CED), Brac University, and Subir and Malini Chowdhury Center for Bangladesh Studies at the University of California, Berkeley, 2021)
This study focusses on the workers from the ready-made garment (RMG) sector of Bangladesh who are particularly vulnerable to the transitory shock to the Covid-19 Pandemic in the sector. The data of the study was collected from a total of 1,038 garment workers in Bangladesh over phone calls from June 30 to July 13, 2020. Among the 906 workers who were still employed in February 2020, 140 reported that their current employers were laying off workers since March 2020 after the pandemic broke out in Bangladesh. The findings of the study reflected workers’ experience during pandemic in terms of their income, savings and food habit along with their perception of risks due to COVID-19, and precautionary measures that factories had taken to stop the spread of the virus among workers.